Improvement of methods of interception of enemy UAVs - I. S. Aftanaziv; I. G. Svidrak; L. I. Shevchuk; O. I. Strogan; L. R. Strutynska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології, 2023)
The main result of this work is the creation of a methodology for determining the coordinates, velocities and trajectories of spatial movements of moving objects by means of kinematic design and the development of principle schemes for the optimal placement of radar search equipment for the successful detection of enemy UAVs. Its purpose is to increase the defense capability of military units, populated areas of Ukraine and their infrastructure by resisting attacks by attack and sabotage reconnaissance unmanned aerial vehicles (UAVs). The protection scheme is based on the determination of coordinates, movement speeds and trajectories of spatial movements of enemy aircraft by means of kinematic design. The established coordinates of enemy UAVs are reported to command posts equipped with liquidator drones (kamikaze) and small arms or to control points of anti-aircraft missile systems (SAMS), which eliminate these aircraft. The proposed improvement of the widespread method of radar search for moving objects is based on the introduction of additional search radar equipment and mathematical apparatus for precise calculations of coordinates and parameters of spatial movements of moving objects by means of kinematic design. Two paired radar search systems, equipped with modern high-speed computing equipment with appropriate software, are able to "screen out" false return electromagnetic signals. This makes it possible to clearly single out the wanted moving object and subsequently track its movement in space. Corresponding mathematical dependencies are proposed for calculating the distance of a moving object to radar stations, its coordinates in the introduced orthogonal coordinate system, speed and acceleration of movement, that is, instantaneous coordinates and parameters of spatial movements of moving objects. This makes it possible to increase the effectiveness of detecting enemy attack and sabotage-reconnaissance unmanned aerial vehicles, including Iranian-made drones of the Sahed-136 model.